ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT (Elaeis guineensis Jacq.) di KECAMATAN WARU KABUPATEN PENAJAM PASER UTARA (Income Analysis of Oil Palm Farming (Elaeis guineensis Jacq.) in Waru Subdistrict, Penajam Paser Utara District) - DEVI ALFIYANTI PRATIWI; SYARIFAH MARYAM; SITI BALKIS (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2020)
A part of community in Waru Subdistrict cultivate oil palm.  This study aimed to determine the costs of production, revenue, income, and revenue/cost ratio of oil palm farming. The research was conducted from June to August 2018 in Waru Subdistrict, Penajam Paser Utara District. The sampling method was purposive sampling. This research collected primary and secondary data.  Data analysis were done to calculte the production costs, revenue, income, and R/C ratio. The results of research showed the average of production costs of oil palm farming was as much as IDR5,449,786.00 year-1 ha-1. The average of revenue of oil palm farming was as much as IDR25,332,427.00 year-1 ha-1. The average of income of oil palm farming was as much as IDR19,882,641.92 year-1 ha-1. The oil palm farming in Waru Subdistrict is economically profitable based on the value of  R/C ratio as many as 4,44 or greater than 1. This meant that for every cost additional of  IDR1,000.00  by farmer will generate the income additional of Rp4,440.00.